2019
DOI: 10.1088/2057-1976/ab0953
|View full text |Cite
|
Sign up to set email alerts
|

Parametric characterization of penumbra reduction for aperture-collimated pencil beam scanning (PBS) proton therapy

Abstract: Recently, a commercial treatment planning system (TPS) has implemented aperture collimators for PBS dose calculations which can serve to reduce lateral penumbra. This study characterized the variation in magnitude of lateral penumbra for collimated and un-collimated PBS fields versus the parameters of air gap, depth, and range shifter thickness. Comparisons were performed in a homogenous geometry between measured data and calculations made by a commercial TPS. Beam-specific target volumes were generated for co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
50
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 22 publications
(58 citation statements)
references
References 15 publications
(27 reference statements)
6
50
0
Order By: Relevance
“…The average lateral penumbra was 10 mm at 15 cm depth when using AA for our system. Meas et al 16 also reported a similar result of lateral penumbra of 8.5 mm when using brass aperture with their measurement condition of range 23.5 g/cm 2 and modulation width 23 g/cm 2 with 7.5 cm WET range shifter. These values are equivalent to those for conventional linacs.…”
Section: Discussionsupporting
confidence: 57%
See 4 more Smart Citations
“…The average lateral penumbra was 10 mm at 15 cm depth when using AA for our system. Meas et al 16 also reported a similar result of lateral penumbra of 8.5 mm when using brass aperture with their measurement condition of range 23.5 g/cm 2 and modulation width 23 g/cm 2 with 7.5 cm WET range shifter. These values are equivalent to those for conventional linacs.…”
Section: Discussionsupporting
confidence: 57%
“…The maximum lateral penumbra reduction by AA was 10.4 mm at 5 cm WET depth for the 10 cm cube target. However, Meas et al 16 reported penumbra reduction of ~4 mm at 5 cm depth for 10 × 10 cm 2 field size, when they were using range shifter of 40 mm WET with brass aperture. The reason for this large discrepancy in penumbra reduction is that the spot sigma at isocenter varied from ~7.3 to 3.2 mm for the IBA system with long beam line, 28 compared to ~19 to 3.9 mm for our system.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations